Penguatan Identitas Lokal melalui Perencanaan Monumen Ikan Lele dan Ikan Nila sebagai Simbol Kearifan Lokal di Desa Aik Bukaq - Evayanti, Restusari; Dwi Saputra, Wahyu; Awalul Putra, Zainury; Salsa Ramdini, Novi; Bondan Andrianto, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This community service program aims to strengthen the local identity of Aik Bukaq Village through the planning and construction of Catfish and Tilapia Monuments. The village is recognized as a center for freshwater fish farming, which serves not only as the primary economic resource but also embodies cultural values passed down through generations. The monument is envisioned as a visual symbol of this local wisdom, while also functioning as a tourist attraction supporting the sustainable development of the village. The monument's design was developed through a participatory approach, involving the local community in every stage of planning, from initial concept to final design. The statues of catfish and tilapia, as the monument’s central elements, represent two species essential to the village’s economy and reflect local values such as hard work, sustainability, and harmony with nature. In addition to serving as a village landmark, the monument includes educational facilities with information panels explaining the importance of fish farming and environmental preservation. This program aims to foster a sense of pride and ownership within the community toward the monument, while also strengthening the local identity, which is increasingly recognized at both regional and national levels. Furthermore, the program is expected to boost tourism, positively impacting the village’s economy and raising awareness of the importance of preserving cultural heritage. As a result, the Catfish and Tilapia Monuments will become a tangible representation of efforts to strengthen the local identity of Aik Bukaq Village, reflecting a collective commitment to sustainable cultural and environmental preservation.